The Effect of Organizational Climate on Employee Job Satisfaction at PT. Persada Crown in Jakarta - Rusmawati Rusmawati; Hamsinah B (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of organizational climate on employee job satisfaction at PT. Mahkota Persada in Jakarta. The method used is explanatory research with a sample of 60 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study of organizational climate variables obtained an average score of 3.735 with suitable criteria. The employee job satisfaction variable received an average score of 3.777 with good standards. Organizational climate has a positive and significant effect on employee job satisfaction with the regression equation Y = 10.246 + 0.737X. The correlation coefficient value of 0.803 or has a strong relationship with a determination value of 64.4%. Hypothesis testing obtained a significance of 0.000 <0.05.